Pengaruh Profitabilitas, Good Corporate Governance, Dan Konservatisme Akuntansi Terhadap Financial Distress Pada Perusahaan Pertambangan Yang Terdaftar Di BEI Periode 2021-2023 - Nur Aisyah Basri (Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2023)
This research uses quantitative research. This study aims to determine the effect of profitability, good corporate governance, and accounting conservatism on financial distress in mining companies listed on the Indonesia Stock Exchange. The independent variable in this study is financial distress. The data used in this study are annual reports and sustainability reports obtained from the Indonesia Stock Exchange website and related company websites. The number of research samples was 51 samples from 17 companies listed on the Indonesia Stock Exchange for the period 2021-2023, with a purposive sampling technique. The type of data in the study is secondary data. The analysis used is descriptive statistical analysis, classical assumptions, and hypotheses with the help of Statistical Package for Special Science (SPSS). The results of this study indicate that return on equity has a negative and insignificant effect on financial distress, and institutional ownership has a positive and significant effect on financial distress. While managerial ownership, foreign ownership, and accounting conservatism have a negative and significant effect on financial distress.